2006
DOI: 10.1177/1934578x0600100813
|View full text |Cite
|
Sign up to set email alerts
|

Pregnane Glycosides

Abstract: Pregnane glycosides constitute a class of compounds widely distributed in the plant kingdom. Many of them have shown either anticarcinogenic or cancer inhibitory properties, besides other useful biological activities. New chromatographic techniques and advances in spectroscopic and spectrometric methods have accelerated the purification and structure determination of novel glycosides of this series. A compilation of the pregnane glycosides isolated from 1995 until the middle of 2005, along with their physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 137 publications
(130 reference statements)
1
22
0
Order By: Relevance
“…Pregnane glycosides are naturally occurring sugar conjugates of C 21 steroidal compounds, isolated from various plants and many show anticarcinogenic properties [ 45 ]. Pregn-5-ene-3β,16β,20(R)-triol 3-O-(2,6-di-O-α-L-rhamnopyranosyl)-β-D-glucopyranoside ( 42 ) and pregn-5-ene-3β,16β,20(R)-triol 3-O-β-D-glucopyranoside ( 43 ) were extracted from the fruits of desert date ( Table 5 ; Figure 4 ) [ 28 ].…”
Section: Phytochemicals Isolated From Desert Datementioning
confidence: 99%
“…Pregnane glycosides are naturally occurring sugar conjugates of C 21 steroidal compounds, isolated from various plants and many show anticarcinogenic properties [ 45 ]. Pregn-5-ene-3β,16β,20(R)-triol 3-O-(2,6-di-O-α-L-rhamnopyranosyl)-β-D-glucopyranoside ( 42 ) and pregn-5-ene-3β,16β,20(R)-triol 3-O-β-D-glucopyranoside ( 43 ) were extracted from the fruits of desert date ( Table 5 ; Figure 4 ) [ 28 ].…”
Section: Phytochemicals Isolated From Desert Datementioning
confidence: 99%
“…In these molecules, the sugar moiety is mostly linked at the C-3 position of the aglycone and generally occurs as a linear rather than a branched oligosaccharide chain (Panda et al, 2006). In recent years, several studies have reported that pregnane glycosides have considerable bioactivity, including compounds with antiproliferative (Cioffi et al, 2006;Plaza et al, 2005), cytotoxic (Braca et al, 2002;De Leo et al, 2005;Chen et al, 2010;Waheeda et al, 2011;Al-Massarani et al, 2012), antifungal (Yoon et al, 2011) and antidepressant (Yang et al, 2011) activities.…”
Section: Introductionmentioning
confidence: 99%
“…The available literature reveals that more than 400 Indian plant species have hypoglycemic potential [ 7 , 8 ]. Wattakaka (W.) volubilis is in the family asclepiadaceae and is grown throughout the hotter parts of India [ 9 ]. The leaf parts of the plant are used traditionally as medicines to treat rheumatic pain, cough, fever, severe cold and dyspepsia.…”
Section: Introductionmentioning
confidence: 99%